ICT Competencies among School Teachers: A Review of Literature - Ai Yieng Wong; Khadijah Daud (Intelektual Pustaka Media Utama, 2018)
The rapid development of information and communication technology (ICT) in education has attract the interest of the Malaysia's Ministry of Education. Ministry aims to have all teachers received ICT training and to integrate ICT in teaching and learning in the classroom. Teachers as the driving force for ICT literate society must prepare themselves with knowledge and skills in ICT. Different competency among teacher in mastering the skills and knowledge of ICT requires a benchmark to help them to know their personal ability. National Educational Technology Standards for Teachers (NETS-T) recommended by the International Society for Technology in Education (ISTE) is a benchmark that can support and enhance teaching and learning in education. This paper attempts to examine the relevant literature review of ICT competency of teachers in the country and abroad. Teachers who successfully meet NETS-T should be a guide to others while any criticism should make changes for the better.